2004
DOI: 10.1111/j.1365-2141.2004.05107.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signalling‐1 gene silencing in acute myeloid leukaemia and human haematopoietic cell lines

Abstract: Summary The aim of this study was to investigate whether the suppressor of cytokine signalling (SOCS)‐1 can act as a tumour suppressor when functioning as a negative regulator of the Janus family tyrosine kinases (JAKs), which have been reported to play important roles in leukaemogenesis. For this purpose, we carried out molecular analysis of the SOCS‐1 gene in human acute myeloid leukaemia (AML) and human haematopoietic cell lines. Sequencing alterations in the coding region were found in two of 90 primary AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 46 publications
4
50
0
2
Order By: Relevance
“…These results were confirmed by sequencing, suggesting that methylation within SOSC1 exon 2 might not be necessarily involved in regulation of gene transcription. The lack of impact of SOSC1 exon 2 methylation on gene expression was also shown by Watanabe et al (2004). In the two cell lines HL60 and U937, where complete methylation of CpG islands within SOCS1 exon 2 was present, there was still a substantial expression of SOCS1 (Fig 1, Watanabe et al, 2004), thus showing an incomplete correlation between methylation and gene silencing.…”
Section: Daimentioning
confidence: 90%
See 3 more Smart Citations
“…These results were confirmed by sequencing, suggesting that methylation within SOSC1 exon 2 might not be necessarily involved in regulation of gene transcription. The lack of impact of SOSC1 exon 2 methylation on gene expression was also shown by Watanabe et al (2004). In the two cell lines HL60 and U937, where complete methylation of CpG islands within SOCS1 exon 2 was present, there was still a substantial expression of SOCS1 (Fig 1, Watanabe et al, 2004), thus showing an incomplete correlation between methylation and gene silencing.…”
Section: Daimentioning
confidence: 90%
“…Later reports, however, focussed on CpG islands in the 5¢UTR. We have recently shown that MSP with primers located in exon 2, as described by Watanabe et al (2004), detected methylation in five of 12 normal peripheral blood and two of three normal marrow samples . These results were confirmed by sequencing, suggesting that methylation within SOSC1 exon 2 might not be necessarily involved in regulation of gene transcription.…”
Section: Daimentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the patients studied by the second group, whose samples demonstrated hypermethylated SHP1, had leukemia characterized by t(8;21) or inv (16), also known as core factor binding leukemia (Table 4). SOCS1 hypermethylation was frequently detected in AML patient samples by two groups [64,65] but not by two other groups [58,63] (Table 4). Only the first group [64] reported correlation with karyotype (Table 4).…”
Section: Hypermethylation Of Stat Inhibitors In Acute Leukemiasmentioning
confidence: 99%